Biosynthesis, evolution and ecology of microbial terpenoids. Issue 2 (6th October 2021) - Avalos, Mariana; Garbeva, Paolina; Vader, Lisa; van Wezel, Gilles P.; Dickschat, Jeroen S.; Ulanova, Dana
Abstract : Terpenoids have diverse bioecological roles in all kingdoms of life. Here we discuss the evolution and ecological functions of microbial terpenoids and their possible applications. Abstract : Covering: through June 2021 Terpenoids are the largest class of natural products recognised to date. While mostly known to humans as bioactive plant metabolites and part of essential oils, structurally diverse terpenoids are increasingly reported to be produced by microorganisms. For many of the compounds biological functions are yet unknown, but during the past years significant insights have been obtained for the role of terpenoids in microbial chemical ecology. Their functions include stress alleviation, maintenance of cell membrane integrity, photoprotection, attraction or repulsion of organisms, host growth promotion and defense. In this review we discuss the current knowledge of the biosynthesis and evolution of microbial terpenoids, and their ecological and biological roles in aquatic and terrestrial environments. Perspectives on their biotechnological applications, knowledge gaps and questions for future studies are discussed.